2022
DOI: 10.1007/s41324-022-00479-w
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability and COVID-19 in Maringá, Brazil

Abstract: This research explores the relationship between COVID-19 and social vulnerability on an intra-urban scale. For this, two composite indicators of social vulnerability have been constructed. The composite indicator constructed by the Benefit-of-the-Doubt considers spatial heterogeneity. It weakly captures the conceptually most significant individual indicator of social vulnerability ( R =-0.39), as it overestimates the above-average performance sub-indicators. The composite indicator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…In Figure 9, we see a relation between a high VI and an increased number of deaths indicating a successful application of the VA. This correlation has also been confirmed in other studies [36]. Still, some differences can be seen.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In Figure 9, we see a relation between a high VI and an increased number of deaths indicating a successful application of the VA. This correlation has also been confirmed in other studies [36]. Still, some differences can be seen.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the correlation between COVID-19 and VI was influenced by the creation of the composite indicator. In addition to the impact of different weighting methods, the selection of indicators is also important [36]. In our case, important indicators are missing due to the lack of data at the municipality level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriation of the system by researchers in these areas favors the understanding and elaboration of public policies that allow for reductions in social vulnerabilities [84], the equitable distribution of public infrastructure in cities [85], improvements in public healthcare services [86], making better decisions in custody hearings [87], promoting the digital maturation of companies, achieving opportunities and avoiding market threats [88], and improving accessibility to healthcare facilities [89], among others.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings from the studies of vulnerability-relevant factors for COVID-19 have also confirmed our results. Living in high-density populations causes the spread of COVID-19 due to crowded areas and high physical contact with other people ( 36 38 ). Furthermore, vulnerable groups ( aged 65 years or older, aged 17 years or younger, older than age 5 with a disability, and single-parent households) and public health infrastructure ( number of healthcare facilities in the area ) were the other considerable domains and indicators with the highest weight.…”
Section: Discussionmentioning
confidence: 99%